The ethicality of conservative management of chronic kidney disease. (2nd March 2019) - Ellis, Peter
Abstract : Conservative management of diseases can reduce healthcare costs and pressures on resources. However, the ethicality of conservative management is often questioned by those who perceive it as a means of rationing, or even denying, care to some sections of society. Peter Ellis explores conservative management, and considers whether it is an ethical treatment option for patients with chronic kidney disease